The Role of Islamic Education in Building Interreligious Tolerance in Indonesia - Muh Habibulloh (Pondok pesantren As-salafiyah As-Safi'iyyah, 2024)
Islamic education plays a vital role in fostering interreligious tolerance in Indonesia, a country renowned for its immense cultural and religious diversity. This study aims to analyze how Islamic education contributes to the creation of interreligious tolerance through the integration of tolerance values into curricula, teaching methods, and school activities. The research employs a library research methodology by examining various literature sources, including the Qur'an, Hadith, and studies on Islamic education and tolerance. The findings indicate that profound Islamic teachings on pluralism—such as the principle of rahmatan lil ‘alamin (mercy to all creation), respect for differences, and the prohibition of religious coercion—provide a strong foundation for building tolerance. Islamic education that incorporates these values into both formal and informal learning processes can help students understand the importance of coexisting harmoniously with people of different faiths. However, challenges such as the politicization of religion and biases against pluralism remain significant obstacles. This study underscores the importance of strengthening multicultural education, providing teacher training, and leveraging technology to support more inclusive and tolerant learning practices. Consequently, Islamic education holds great potential to cultivate a young generation that is tolerant, empathetic, and committed to preserving harmony in a diverse society.